2012
DOI: 10.1161/hypertensionaha.111.190413
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Onset of Renal Sympathetic Nerve Activation in Rabbits Fed a High-Fat Diet

Abstract: Abstract-Hypertension and elevated sympathetic drive result from consumption of a high-calorie diet and deposition of abdominal fat, but the etiology and temporal characteristics are unknown. Rabbits instrumented for telemetric recording of arterial pressure and renal sympathetic nerve activity (RSNA) were fed a high-fat diet for 3 weeks then control diet for 1 week or control diet for 4 weeks. Baroreflexes and responses to air-jet stress and hypoxia were determined weekly. After 1 week of high-fat diet, calor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
111
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(129 citation statements)
references
References 44 publications
12
111
1
1
Order By: Relevance
“…In rabbits fed high-fat diets, body weight, plasma insulin and leptin concentrations, mean arterial pressure, heart rate, and renal sympathetic nerve activity were all increased after 1 week. 1 Mean arterial pressure and body weight continued to increase over 3 weeks of high-fat diet, whereas heart rate and renal sympathetic nerve activity did not change further. Arterial baroreflex control of renal sympathetic nerve activity was attenuated from the first week of the high-fat diet.…”
Section: Obesity-related Hypertensionmentioning
confidence: 91%
“…In rabbits fed high-fat diets, body weight, plasma insulin and leptin concentrations, mean arterial pressure, heart rate, and renal sympathetic nerve activity were all increased after 1 week. 1 Mean arterial pressure and body weight continued to increase over 3 weeks of high-fat diet, whereas heart rate and renal sympathetic nerve activity did not change further. Arterial baroreflex control of renal sympathetic nerve activity was attenuated from the first week of the high-fat diet.…”
Section: Obesity-related Hypertensionmentioning
confidence: 91%
“…As an alternative to visually identifying artifacts on traces, some investigators have restricted SNA recordings to a few hours a day when the animals can be monitored for animal movement (1,19,20). This has clear advantages and can provide useful data regarding the disease state and responses to acute experimental manipulations in conscious animals.…”
Section: Electromyogram or Animal Movementmentioning
confidence: 99%
“…4,5 We have recently shown that the renal sympathetic nerve activity (RSNA) and BP increases in the first few days of consuming a high-fat diet (HFD) in rabbits can be largely reversed by a leptin antagonist given intracerebroventricularly (ICV). [6][7][8][9] In contrast, ghrelin secreted by the stomach activates arcuate neurons containing neuropeptide Y and agouti-related protein and has been shown to suppress sympathetic activity, decrease BP, and stimulate appetite.10,11 Thus, both leptin and ghrelin may play a key role in the association between obesity and hypertension and may also be involved in the hypertension programmed by a maternal HFD (m-HFD).The purpose of this study was to examine the effect of an m-HFD during development on arterial pressure and RSNA and the central sympathetic effects of leptin and ghrelin in offspring. We used a rabbit model in which an HFD induces elevated BP and RSNA.…”
mentioning
confidence: 99%
“…We used a rabbit model in which an HFD induces elevated BP and RSNA. [6][7][8][9] We hypothesized that offspring exposed to an HFD during development would retain greater deposits of fat and show a selective leptin-resistant phenotype Abstract-Exposure to maternal obesity or a maternal diet rich in fat during development may have adverse outcomes in offspring, such as the development of obesity and hypertension. The present study examined the effect of a maternal high-fat diet (m-HFD) on offspring blood pressure and renal sympathetic nerve activity, responses to stress, and sensitivity to central administration of leptin and ghrelin.…”
mentioning
confidence: 99%
See 1 more Smart Citation